Peran Desa Wisata Bahari Dalam Meningkatkan Kesejahteraan Masyarakat Pesisir Di Kepulauan Labengki Kabupaten Konawe Utara Sulawesi Tenggara - Indah Harlina; Jum Anggriani; Tetti Samosir (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Indonesia is a maritime country, where the sea area is larger than the land area. To realize the country's goal of becoming a prosperous country, as stated in the Preamble to the fourth paragraph of the 1945 Constitution, the Minister of Maritime Affairs and Fisheries Regulation No. 93/PERMEN-KP/2020 concerning Maritime Tourism Villages was issued, in addition to that there is also a regional regulation for Konawe Regency. North No. 2 of 2016 concerning the Master Plan for Regional Tourism Development for North Konawe Regency for 2016-2026 and also North Konawe Regent Decree No. 86 of 2022 concerning Designation of Developing Classification Tourism Villages and Pilot Classification Tourism Villages in North Konawe Regency. This is one of the efforts made by the government to improve the standard of living of the people living in the maritime village. The research method used is descriptive analysis with normative and empirical juridical approaches. The results of the study are that the role of tourist villages in the Labenkie Islands is very helpful in improving the welfare of the Labengki peopleKeywords: Tourism, Nautical villages, Welfare AbstrakNegara Indonesia adalah negara bahari, dimana luas laut lebih besar daripada luas daratan. Untuk mewujudkan tujuan negara menjadi negara yang sejahtera, sebagaimana tercantum dalam Pembukaan Alinea keempat Undang-Undang Dasar 1945, maka dikeluarkannya Peraturan Menteri Kelautan dan Perikanan No.93/PERMEN-KP/2020 tentang Desa Wisata Bahari, selain itu ada juga Peraturan daerah Kabupaten Konawe Utara No. 2 Tahun 2016 tentang Rencana Induk Pengembangan Pariwisata Daerah Kabupataen Konawe Utara tahun 2016-2026 dan juga Keputusan Bupati Konawe Utara No 86 Tahun 2022 tentang Penetapan Desa Wisata Klasifikasi Berkembang dan Desa Wisata Klasifikasi Rintisan di Kabupaten Konawe Utara. Hal ini merupakan salah satu upaya yang dilakukan oleh pemerintah dalam meningkatakan taraf hidup masyarakat yang berada di desa bahari tersebut. Metode penelitian yang digunakan adalah deskriptif analisis dengan pendekatan yuridis normatif dan empiris. Adapun hasil penelitian yaitu bahwa peran desa wisata di kepulauan Labenkie sangat membantu dalam meningkatkan kesejahteraan masyarakat Labengki.Kata Kunci: Pariwisata, Desa bahari, Kesejahteraan